The protective effect of vitamin C on growth, digestive enzymes, immune response, and gill histology in Caspian roach (Rutilus rutilus caspicus) under diazinon stress - Mahmud Nikjoo; Mohammad Farhangi; Rahman Patimar; Hossein Adineh; Maryam Alizadeh (Aquaculture Reports, 2023)
In recent years, the increase in the use of agricultural pesticides has endangered the production of marine creatures. However, exposing farmed creatures to water contaminated with pesticides is one of the current challenges. This study aims to investigate the defensive impact of diets containing varying amounts of vitamin C on the growth, digestive enzyme activity, immune response, and resistance of Caspian roach (Rutilus rutilus caspicus) exposed to diazinon. Fish (average weight: 1.12 ± 0.17 g) were fed diets containing 0 (control; C0), 500 (C1), 1000 (C2), and 1500 (C3) mg/kg of vitamin C for 56 days. Then they were exposed to diazinon stress for 14 days (0.32 mg/liter). The highest final weight and lowest feed conversion ratio were obtained in fish fed a diet containing vitamin C. The highest protease activity and lowest amounts of lipase and amylase were observed in the C3 group. At the end of the feeding period, lysozyme activity, total immunoglobulin amount, and complement (ACH50) in the C3 treatment were significantly higher than in the control treatment. After the stress period, lysozyme and complement activity were higher in all groups fed vitamin C supplements than in the control treatment. The highest levels of stress indicators (cortisol and alkaline phosphatase) were detected in the control group before and after stress. Based on the preparation of gill tissue sections, most lesions included edema, hyperplasia, adhesion of secondary lamellae, and necrosis of gill-covering cells. Overall, the results indicate that adding vitamin C to the diet can be used as a sustainable bioremediation tactic and reduce the adverse effects of diazinon exposure in Caspian roach.